Eksplorasi Berpikir Kritis Siswa SMP Pada Soal PISA Konteks Palembang Berdasarkan Kemampuan Awal - Dyego Ostian (Universitas Muhammadiyah Palembang, 2026)
This study aimed to describe the critical thinking processes of junior high school students in solving PISA-based algebra problems using the context of Palembang based on their prior ability levels. The study employed a qualitative descriptive approach with six students selected purposively and categorized into high, medium, and low ability groups. The instrument consisted of three PISA-type algebra problems. Data were analyzed based on mathematical critical thinking indicators, including interpretation, analysis, evaluation, inference, and explanation. The results showed that students with low ability only demonstrated the ability to understand problems, while students with medium ability reached the stages of analysis and reasoning but were not consistent in evaluation and conclusion. In contrast, high-ability students demonstrated all critical thinking indicators completely and systematically. Furthermore, higher cognitive levels of the problems affected students’ performance, where low and medium ability students showed a decline, while high-ability students remained consistent.